Implications of New Standards on Technical Diagnostics and Control Implementation for the Gas Transmission System Efficiency - Karpash, M.O.; Oliynyk, A.P.; Kogut, G.M.; Klyun, A.M. (Science and Innovation, 2024)
Introduction. Ukrainian gas transmision system (GTS) as a part of the whole oil and gas complex takes the important role in energy security of the state. Taking into consideration the aging and physical deterioration procesess, a lot of attentionn today is paid to the question of ensuring GTS relaible operation and maintenance. Problem Statement. All innovations and technicaogical achievements, implemented into GTS are impossible without a detailed study of productivity of GTS facilities, the costs for implementing the new standards, and the costs for eliminating the emergency situations’ consequences. Purpose. Assessment and evaluation of data on efficiency of Ukrainian GTS, based on the implementation of new standards on technical diagnostics and control (TDC), influencing significantly on the operation of GTS facilities. Materials and Methods. For the analysis, we chose the complex mathematical model, allowing to determine the qualitative relationship between the productivity of GTS facilities, the costs of implementing new standards for technical diagnostics and control, and the costs for eliminating the consequences of economic, environmental and other impacts. Besides the expert evaluation method and numerical Runge-Kutt methods were applied for practical use of the proposed model. Results. The efficiency of GTS operation, according to the proposed model, depends on the costs, spent for the implementation of standards. Among the benefits for increasing of standards expenditures are the growth of emergency response funding, which tends to decreasing in timely manner. Calculation results showed the adequacy of the proposed experts’ assessment model according to the question of objectivity, impartiality and consistency of expert opinions. Conclusions. The complex of mathematical calculations maintained the qualitative picture of the relationship between selected characteristics. The new approach to analysing data on Ukrainian GTS efficiencywas suggeted, presenting the mechanism for establishing the dependencies between costs of implementing new standards and costs for eliminating emergency situations.